Alternative Instruments for Addressing the Syrian Refugee Problem in Lebanon. (c2017) - Antossian, Markrid Stepan (2017)
This thesis seeks to contribute to the literature on displaced populations, taking the situation of the displaced Syrians in Lebanon as a case study. The thesis investigates three distinct scenarios for addressing the situation of the displaced Syrians in Lebanon: 1) absorption (or integration) into the local hosting communities, 2) voluntary repatriation back to Syria, and 3) resettlement in a third country. As a backdrop to the analysis, the thesis brings to the forefront the ramifications of the situation created by large numbers of displaced Syrians on: hosting communities, the Lebanese state and Lebanon’s confessional system, and the displaced populations themselves. A principal aim of the thesis is to explore the pros and cons of each of the three aforementioned settlement/resettlement strategies. Based on the carried out analysis, the thesis concludes that resettling large numbers of displaced Syrians in third countries constitutes the most optimum strategy for dealing with this complex problem. The research involves a thorough survey of available secondary work on displacement, especially the rights and duties under international law of displaced populations, as well as an examination of primary sources, particularly the studies and reports of pertinent international agencies.